Motion of mitral apparatus in hypertrophic cardiomyopathy with obstruction. Issue 7 (July 1976) - Rodger, J C
Abstract : Motion of the mitral apparatus in hypertrophic cardiomyopathy with obstruction was investigated by conventional single dimensional and multidimensional echocardiography. In systole, anterosuperior displacement of the posterior papillary muscle, failure of mitral valve closure, and anterior motion of both mitral leaflets were shown. The anterior leaflet was seen to impinge on the posterior papillary muscle but not on the interventricular septum in systole. The abnormality of the single dimensional mitral echogram, previously ascribed to systolic anterior motion of the mitral anterior leaflet, was found to be a complex of echoes from the chordae tendineae, the papillary muscle, and, furthest from the septum, the mitral anterior leaflet. It is concluded that systolic anterior motion of the mitral anterior leaflet is of smaller amplitude than others have suggested, and that obstruction to left ventricular outflow in hypertrophic cardiomyopathy is produced by systolic contact between the mitral anterior cusp and the posterior papillary muscle. The theory is put forward that displacement of the posterior papillary muscle above and in front of the mitral leaflets produces chordal slackening, and that it is displacement of the chordae tendineae by the blood flowing to the aortic root during left ventricular ejection, which is responsible for systolic anterior motion of the mitral leaflets.